Trypanosoma cruzi infection enhances polyreactive antibody response in an acute case of human Chagas' disease. - Grauert, M R (1993)
The kinetics of antibody response in an acute case of human Chagas' disease was investigated. Hypergammaglubulinaemia appeared at day 17 of infection, and persisted after 66 days of infection, at which time parasitaemia became undetectable. Titration of immunoglobulins showed that the three principal isotypes were involved in the response, emphasizing polyclonal B cell activation. Total IgA was detected before total IgM, and the latter before total IgG. High titres of autoantibodies were found among IgM and IgG subclasses. IgA was also the first isotype to be detected among specific anti-Trypanosoma cruzi antibodies. However, the maximal parasite antibody response was attained after 30 days of infection for all isotypes. With regard to possible cross-reactivity between molecules of host and parasite, adsorption experiments on T. cruzi-specific immunosorbent were designed. Specific antibodies, present in the eluates, also recognized natural antigens, especially laminin. In order to characterize the alpha-galactose epitope of laminin, adsorption experiments on sheep erythrocytes were performed, and revealed the possible presence of another epitope on the glycoprotein. Our results indicate that in the case of Chagas' disease investigated here, polyclonal activation occurred; moreover, they suggest that molecular mimicry may play a role by increasing autoantibodies, probably via a parasite-driven mechanism.